On-Road Performance Evaluation of an Electric Vehicle for Battery Consumption and Driving Behavior Detection in Real Operating Conditions of Batu Pahat, Johor - Zaifuddin, Nurul Haziqah; Mohamad, Khairul Anuar; Alias, Afishah; Mohd, Mohd Shafiee; Kasim, Kasrul Nazrin; Abdullah, Norisham (Evolution in Electrical and Electronic Engineering, 2021)
Internal combustion engine (ICE) transportation plays a significant role in air pollution, global warming and harmful to human health. Thus, environmental awareness has led to shifting towards the use of electric vehicle (EV) technology that is much more environmentally friendly. This study analyzes parameters affecting EV’s performance in terms of energy consumption. The on-road performance evaluation has recorded parameters such as speed, distance travel, temperature, load factor and battery consumption during multiple road conditions to estimate EV performance in battery efficiency. This study further evaluates the relationships between the acceleration and velocity of the vehicle on different road gradients using a developed motion sensor device.  A google sheet with internet of things-based data logger (IOTDL) system was developed to collect acceleration and gyroscope data for driver behaviors such as accelerating, decelerating or turning direction using VibrationData Toolbox by Matlab. Based on the on-road results, battery consumption level linearly decreased over trip distance with an almost constant drop rate. With a maximum speed of 60 km/h, the EV can run at a maximum 500 km range per one battery cycle. In addition, the battery consumption increased with increasing speed and load weight over trip distance. Meanwhile, the evaluation also proved that EV saves more energy and fuel cost by 78.8% than an ICE vehicle. Furthermore, road curve with smaller radius and changing direction event tend to accelerate and decelerate repeatedly compared to flat straight road in terms of driving behavior. Thus, this study plays an important role in providing drivers an indicator that helps them to reduce their poor driving habits while encouraging helpful tips to optimize EV energy consumption.